Diet of Leptodactylus ocellatus (Linnaeus, 1758) (Anura: Leptodactylidae) in a western swamp of Argentina - Sanabria, Eduardo A. (2005)
This work study the diet of Leptodactylus ocellatus from the swamp of Zonda, San Juan, in western Argentina. We analyze 41 stomaches, preys were classified and indiviudals were measured (wide and long), to calculate their volume with the sphere ellipsoid, furthermore, the frequency and the abundance was also considered. Indexes of diversity, of similarity, niche width and relative importance (IRI), were calculated. The more important preys were: Hymenoptera, Anura, Coleoptera. The preys with more percentage of presence were the Hymenoptera Formicidae (22,4%). Relationship among the predator’s width mouth and the average size of the prey was not significant. Diet in both sexes were similar.